1997
DOI: 10.1073/pnas.94.5.1852
|View full text |Cite
|
Sign up to set email alerts
|

Type III collagen is crucial for collagen I fibrillogenesis and for normal cardiovascular development

Abstract: Type III collagen is a fibrillar forming collagen comprising three ␣1(III) chains and is expressed in early embryos and throughout embryogenesis. In the adult, type III collagen is a major component of the extracellular matrix in a variety of internal organs and skin. Mutations in the COL3A1 gene have been implicated as a cause of type IV Ehlers-Danlos syndrome, a disease leading to aortic rupture in early adult life. To directly study the role of Col3a1 in development and disease, we have inactivated the Col3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
406
0
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(450 citation statements)
references
References 25 publications
22
406
0
5
Order By: Relevance
“…In animal models, mice homozygous for an inactivated allele of Col3a1 showed a phenotype closely resembling EDS IV, whereas heterozygous mice were phenotypically normal. 31 Late-onset signs in heterozygous mice, however, could not be excluded, because these mice had a limited follow-up period (cf. there are functional changes in bladder tissue of 8-week-old mice heterozygous for a Col3a1 null allele).…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, mice homozygous for an inactivated allele of Col3a1 showed a phenotype closely resembling EDS IV, whereas heterozygous mice were phenotypically normal. 31 Late-onset signs in heterozygous mice, however, could not be excluded, because these mice had a limited follow-up period (cf. there are functional changes in bladder tissue of 8-week-old mice heterozygous for a Col3a1 null allele).…”
Section: Discussionmentioning
confidence: 99%
“…In connective tissues, including blood vessels and skin, collagen type III colocalizes with collagen type I within the same fibril, presumably to regulate the size of collagen type I fibrils (Fleischmajer et al, 1988(Fleischmajer et al, , 1990. In Col3a1Ϫ/Ϫ mutant mice, electron microscopy detected collagen fibrils irregular in size in the skin and the adventitia of the aorta, indicating the necessity for collagen type III for normal collagen fibrillogenesis (Liu et al, 1997). Ultrastructural analysis of mice harboring a targeted disruption of the decorin gene revealed abnormal collagen morphology in decorin-deficient tendon, with coarser fibrils and irregularities in size and shape when compared with wild-type tissue (Danielson et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen type III is a member of the fibrillar collagen family and the second most abundant collagen molecule in tendon. Studies in skin, tendon, and other tissues indicate a role for collagen type III in regulating fibrillogenesis of collagen type I (Fleischmajer et al, 1988(Fleischmajer et al, , 1990Ros et al, 1995;Liu et al, 1997;Birk and Mayne, 1997). Decorin is a small chondroitin-dermatan sulfate proteoglycan consisting of a core protein and a single glycosaminoglycan chain, and is the most abundant proteoglycan in mature tendon (Goh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…uk/genetics/collagen/) 5 match with this model. Although biases related to the screening methods for mutation detection are possible, this mutation spectrum, the analogy with the COL1A1 and COL1A2 mutations spectrum observed in osteogenesis imperfecta (MIM#120150 and 120160, http://www.ncbi.nlm.nih.gov/Omim/), and the findings from a mouse knockout model for COL3A1 6 have long suggested that COL3A1 null alleles could confer attenuated phenotypes. However, in 2001, the study by Schwarze et al 7 questioned these genotype -phenotype correlations.…”
Section: Introductionmentioning
confidence: 99%